Pengembangan Elektornik Modul Dengan Menggunakan Kvisoft Flip Book Maker Padam Kelas XI SMA Negeri 9 Luwu Utara - Rosanti, Mita; Nur Zahrah; Nilam Permatasari; Siti Marwiyah; Nurdin K; M. Zuljalal Alhamdany (Universitas Palangka Raya, 2023)
The aim of this research is to prove the validity and practicality of the electronics modules that use KviSoft Flip Book Maker. The study was conducted at the 9th Luwu North State High School with a 4D model: (1) Phase Definition, (2) Design Phase, (3) Phase Development, and (4) Phase Distribution.After the development of electronic modules using 4D models, the next step is validity and practicality. Specifically, (1) the results of the validation of the electronic product module from the material expert show 100% presentation and belong to a very valid category; (2) the verification results from the media expert show 68% and are belonging to a good or valid Category; and (3) the validity results from a linguist show 82% and come from the category ve (4) In the electronic practicality test of the elevation module, the student's answers are based on calculations of the IF formula using Microsoft Excel. For example, the material aspect receives 3,06 with a good or valid category, the media aspect receivers 3,05 with a well or valid Category, the language aspect receiving 4, 58 with a very good or very valid Category; the illustration aspect receves 2,52 with a valid Category or Aspect, and the instruction unit receives 2,52 of a valid category or Aspects. Based on the results, it can be concluded that the electronic learning module of the Islamic educational material uses valid social media and can be used as a learning medium in practice.